A review of the ethnomedicinal, antimicrobial, and phytochemical properties of Musa paradisiaca (plantain) - Ajijolakewu, Kamoldeen Abiodun (2023)
More people—in both developing and developed countries—now use, and are favourably disposed to, traditional medicine. Musa paradisiaca (plantain) is used extensively in traditional medicine across continents. In this review, we investigated the scientific justification of this extensive usage. Findings in the studies reviewed projects plantain as a veritable source for drug bioprospecting that will be of benefit to scientific research and pharmaceutical industries.